Anastomotic Leak Risk Calculator – Can it be Used to Predict Anastomotic Leaks in Colonic Surgeries? - Chinta, Varsha; Lakshminarayana, Badareesh; Samuel, Roshen (Journal of Coloproctology, 2025)
We aimed to evaluate the Anastomotic Leak Risk Calculator in predicting the outcome of Colonic Anastomosis in right and left sided colonic surgeries at our institution from November 2022 to May 2024. We also evaluated the various variables which may predict the risk of leak pre-operatively and intra-operatively.Patients who underwent colectomy on an emergency/elective basis were included and were followed for 30 days post operatively. Preoperative, intraoperative and post operative data was collected which was used to derive a risk score using the previously developed Anastomotic Leak Risk Calculator.The predictability of occurrence of Anastomotic leak (AL) in colonic surgeries by the Anastomotic Leak Risk Calculator has not been statistically significant. AL percentage in our study was 6.7%. The site of anastomosis significantly effects the probability of occurrence of anastomotic leak. The occurrence of intra operative complications have a significant effect on the preoperative and post-operative anastomotic leak risk score. There is a significant effect of AL on the duration of hospital stay post-surgery and the 30-day outcome of the patient.An accurate assessment of the risk of anastomotic leak is crucial to tailor personalized treatment choices for patients. Various pre-operative and intraoperative factors must be carefully analyzed to decide the further course of action in every patient who requires colonic surgery.
Keywords: Anastomotic Leak; colonic surgery; post operative complications